The Development of Science Learning Module with Problem Solving Method - Patriksius Arpan; Aunurrahman Aunurrahman; Fadillah Fadillah (JETL (Journal of Education, Teaching and Learning), 2018)
This study aims to produce science learning modules with Problem Solving methods that will be used in science learning plant breeding materials, can implement the science learning module Problem-Solving methods and describe the learning outcomes of plant breeding materials using method Problem-Solving in State Elementary School 03 of Hulu Sungai in Ketapang Regency. This research is the development of science learning method using Problem-Solving method by using the development phase of R & D Research adopted by Borg and Gall with module design using ADDIE model, with the research subject is class VI involved 16 students Data obtained through expert design validation questionnaire, expert media materials and experts, interviews, student response questionnaires, and documentation. Furthermore, data analysis is conducted qualitatively and quantitatively.